Habitual caffeine intake affects implant osseointegration: An in vivo study. (7th August 2021) - Omar, Omar; Abuohashish, Hatem M.; Alkhamis, Taleb; Al‐Qarni, Faisal
Abstract: Objectives: This study aimed to evaluate the effect of habitual caffeine (CAF) intake on stability, bone regeneration, and expression of bone markers at the bone‐implant interface. Background: Studies show that habitual CAF alters bone health and remodeling. Yet, there is no information regarding CAF effects on osseointegration of bone‐anchored implants. Methods: Wistar rats were divided into two groups: one received tap drinking water alone (control) and the other received tap water with CAF (300 mg/L). After 12 weeks, their tibiae received screw‐shaped titanium implants. After another 12 weeks, CAF ( n  = 5) and control ( n  = 5) animals were sacrificed and the implant stability was evaluated using a removal torque (RTQ) device. Thereafter, the implants were processed for gene expression analysis, and the implantation sites were harvested for histology. Implants with the surrounding bone were dissected en bloc and subjected to micro‐computed tomography (micro‐CT). Results: The results showed that implants in the CAF group had an 87% significant increase in RTQ compared to the control. Further, micro‐CT revealed a higher proportion of mineralized bone filling the implant threads in the CAF group. The molecular analysis indicated higher expression of bone formation (ALP), remodeling (CatK), and vascularization (VEGF) genes in implant‐adherent cells in the CAF group. Histology suggested increased vascularity in the tissue surrounding the implant in the CAF group. Conclusions: Within the limit of this study, it is concluded that habitual CAF intake conveys a positive, promoting effect on long‐term osseointegration. Clinical studies are worth pursuing to verify this experimental observation.